Características e perfil lipídico da carne em cordeiros alimentados com torta de girassol - Moura, Wemerson Paulino da Silva (2013)
The experiment was carried out at the experimental extation the Federal University of Mato Grosso (UFMT), located at coordinates 15 ° 47'05 "South and 56 ° 04 'west, and 140 m altitude, between the months of July and September 2011. A total of 40 lambs uncastrated male, with average initial body weight (BW) 20.17 ± 2.66 kg and between 3 and 4 months, which were divided into 20 (2 lambs/pen). The experiment was conducted in a completely randomized design with 5 treatments and 8 replications. The experimental diets were formulated based on the dry matter (DM) to obtain a proportion of 40% forage and 60% concentrate. Is was used corn silage and forage sourch where as concentrates were composit by ground corn, soybean meal, urea / ammonium sulfate, mineral mix and sunflower cake (TG), being the last ingredient added to the diet at levels 0%, 7%, 14%, 21% and 28% DM. Diets were formulated to obtain 13,8% crude protein (isonitrogenous) and provide average gain of 200 grams per day. The daily food intake was calculated based on the body weight of the animals were feed truice daily at 8 and 16h, in the form of to mixed ration, and the treatment and monitored daily orts to be maintained at 10% of the offered. Water was provided ad libitum during the experimental period. There was no treatment effect (P>0.05) on meat composition (moisture, protein, lipid and ash), velues observed were 73.32, 22.11, 2.91 and 1.24% respectively. The pH (6.15), the intensity of the yellow meat (-3.54), the amount of red meat (16.09), red intensity fat (46.24), shear force (4.13), cooking loss (23.39) and loin eye area (9.7) also not affected by treatment (P>0.05). The brightness of the meat and fat (L) and proportion of desirable fatty acids (DFA) were affected quadraticly (P<0.05) the levels of sunflower cake in the diets. The lowest estimated intensity G of the meat was 30.52 with the inclusion of 12.5% TG. The lower intensity of L fat was 57.23 to 11.21% inclusion of TG. The lowest estimated proportion of DFA was 71.4 to 10.5% with the inclusion of TG. The intensity of yellow fat, fat thickness, proportion of iso-hexadecanoic fatty acids, linoleic acid, γ-linolenic acid, eicosadienoic, eicosapentaenoic acid, iso-tetradecanoic, palmitoleic, t16-octadecenoic acid, conjugated linoleic acid (CLA) and fatty acid ratio polyunsaturated / monounsaturated fatty acids (PUFA / SFA) was influenced linearly (P<0.05). Found only traces of fatty acids otusílic, undecanoic, tridecanoic anteiso-, lauroleic, octadecadenoic, C21:0, C20:3 n6, eurucic, C20:3 n3, C23:0, lignoceric and nervonic. The sunflower cake added to the diet of lambs up to 28% of total dry matter does not adversely affect its organoleptic and nutritional quality improves, it increases the concentration of CLA and the PUFA / SFA ratio.